Novosti . Novosti . News . Новости - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Reportages on the latest events from the spot; operation on seizing the White House (The House of Soviets). Featured in the program: Filatov, Sergei (Head of Presidential Administration of the the Russian Federation) Репортажи с последних событий в Москве; операция по захвату Белого Дома (Дома Советов). В программе участвуют: Филатов, Сергей (Руководитель Администрации Президента Российской Федерации)